Proximate Composition, Texture Performance and Sensory Evaluation of Lindur Fruit-Potato Simulation Chips Enriched With Shrimp (Penaeus Vannamei) Shell Powder - Diah Ikasari; Ema Hastarini (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2016)
Study aimed to investigate the utilization of shrimp shell powder in the production of lindur fruit-potato simulation chips, which was assessed using proximate composition, texture performance and sensory evaluation parameters. Three different ratios of lindur fruit-potato flour (w/w) (30:70, 40:60 and 50:50), as well as different concentrations of shrimp shell powder (0, 1, 3 and 5%) were used in the formula. The results showed that lindur fruit-potato simulation chips enriched with shrimp shell powder had 3.22-4.42% moisture content, 3.33-4.94% ash content, 3.77-5.83% protein content, 14.59-19.04% fat content, 71.06-76.34% carbohydrate content and 341.4-530.9 g/cm2 hardness. Ratio lindur fruit flour and potato flour of 40:60 as well as 3% of shrimp shell powder was chosen as the best treatment since the formula produced lower hardness, higher protein content and the most crispy and tasty chips preferred by panelists.